Avenue of Saman [sic] Trees, Trinidad, B.W.I .- 20797 - (:unkn) unknown (Photogelatine Engraving Co. Limited, 2010)
The postcard shows an avenue lined with Samaan trees.
Colour: Sepia with hues of brown and green; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Rural roads--Trinidad and Tobago; Albizia saman; Samaan